MONEY POLITICS DALAM TINJAUAN HADIS NABI - Muhammad Nur Shiddiq (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
This article discusses the practice of money politics in a review of the Prophet's hadith. This term Money Politics is not known in Islam, but practices that resemble money politics already exist and are indicated in the hadith of the Prophet with the term risywah. In the period before the Prophet was also found to have occurred this practice, as had been done by Queen Saba to the Prophet Solomon by giving various kinds of gifts with specific purposes. So this paper will review the words of the Prophet about risywah, and how he views such behavior. This paper finds the fact that the risywah perpetrators and risywah recipients will get the curse from Allah and His messenger. In addition, this paper also tries to examine the differences in the matn of the hadith that speak of risywah. It was concluded that the difference occurred because some of these hadith were narrated by bi al-ma'na